Visible light catalytic self-cleaning polytetrafluoroethylene flat membrane and preparation method thereof

By combining the metal organic frame ZIF-67-Co powder with polytetrafluoroethylene dispersive resin and mineralized by FeCl3 solution, a polytetrafluoroethylene flat film with high visible light catalytic efficiency and self-cleaning performance was prepared, and the current solution was solved In some technology, the lack of visible photocatalytic properties of polytetrafluoroethylene flat films has achieved efficient application in wastewater treatment and oil-water separation.

CN119034500BActive Publication Date: 2025-01-07ZHEJIANG SCI-TECH UNIV +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411516086.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-07
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

In the prior art, the polytetrafluoroethylene flat film has poor effect in visible photocatalytic performance, the preparation method is complex and difficult to control, and it is difficult to meet the high requirements of wastewater treatment and oil-water separation.

Method used

The metal organic frame ZIF-67-Co powder is mixed with the polytetrafluoroethylene dispersive resin. After extrusion, stretching and heat setting, the FeCl3 solution is used to mineralize to form polytetrafluoro with visible photocatalytic self-cleaning properties. Ethylene flat film.

Benefits of technology

The polytetrafluoroethylene flat film has high visible light catalytic efficiency and good stability, which can show excellent performance in the fields of wastewater treatment and oil-water separation, and maintain high efficiency in cycle tests, extending the service life of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119034500B_ABST
    Figure CN119034500B_ABST
Patent Text Reader

Abstract

The present invention provides a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane and a preparation method thereof. In the present invention, a metal organic framework powder with visible light catalysis is added to a polytetrafluoroethylene dispersion resin to prepare a primary polytetrafluoroethylene flat membrane with catalytic performance, and then a polytetrafluoroethylene flat microporous membrane with visible light catalytic self-cleaning performance is obtained by mineralization on its surface. The preparation process of the visible light catalytic self-cleaning polytetrafluoroethylene flat membrane of the present invention is simple and low in cost. The obtained visible light catalytic self-cleaning membrane has the characteristics of strong visible light absorption capacity, recyclability, high visible light catalytic efficiency and good stability, and has good prospects in the fields of wastewater treatment, oil-water separation, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of processing and manufacturing of polytetrafluoroethylene flat membranes, and in particular to a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane and a preparation method thereof. Background Art

[0002] With the rapid industrialization, environmental problems have triggered the development of new technologies. Water pollution is one of the main problems facing mankind. The current common technology is to treat water pollution through various membrane elements. Compared with other membrane elements, flat membranes have a larger membrane area and higher flux, which is suitable for the treatment of high-concentration and high-turbidity water bodies. The advantages are compact structure, simple operation, and easy maintenance. In addition, the materials of sewage filtration membranes mainly include polyethersulfone (PES), polyethylene (PE), polypropylene (PP), polyvinylidene fluoride (PVDF) and polytetrafluoroethylene, among which polytetrafluoroethylene membranes can resist almost all strong acids and alkalis and various organic solvents, and have excellent corrosion resistance and thermal stability. They can be used for a long time in the temperature range of -250~260 ℃, so polytetrafluoroethylene membranes play an important role in the field of membrane separation technology.

[0003] In order to further improve the photocatalytic performance of membrane elements and enhance their processing capacity and self-cleaning ability under complex water conditions, visible light catalytic materials can be loaded on membrane materials to effectively improve their thermal stability, catalytic activity and reusability. The prior art patent CN113680220B uses nano-boron carbide with photocatalytic effect and polyvinylidene fluoride to blend, and prepares a polyvinylidene fluoride flat membrane with photocatalytic effect by phase inversion deposition method. However, during blending, the composite material is wrapped in the polymer material, which significantly weakens its photocatalytic performance, and the composite material loaded by the phase inversion method is not firmly bonded to the base membrane, and is easily lost, resulting in a decrease in the photocatalytic performance of the membrane and secondary pollution. Patent CN114177943B is to dissolve the composite photocatalytic material AgCl / MIL-100 (Fe) in Nafion solution and load it on a polytetrafluoroethylene membrane by vacuum filtration to prepare a photocatalytic membrane. Although the iron-based metal organic framework has uniformly distributed iron active sites and aromatic ligand structures, there is a problem of loss of composite photocatalytic materials during long-term use. Patent CN115282787A produces a composite separation membrane with ultraviolet photocatalytic self-cleaning function through a wet phase conversion method. The preparation process has mild conditions and low energy consumption, and has obvious advantages in promotion. However, the energy of ultraviolet light only accounts for about 5% of the energy of sunlight, and the polymer separation membrane ages severely under long-term irradiation of ultraviolet light, which will limit its practical application.

[0004] In summary, the water pollution treatment membrane with visible light catalytic effect in the prior art has either a complex and difficult to control preparation method, or has a poor visible light catalytic effect, which makes it difficult to meet the high requirements of actual wastewater treatment and oil-water separation. Summary of the invention

[0005] The purpose of the present invention is to provide a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane and a preparation method thereof. The preparation process is simple and the cost is low. The prepared visible light catalytic self-cleaning polytetrafluoroethylene flat membrane has the characteristics of strong visible light absorption capacity, recyclability, high visible light catalytic efficiency and good stability, and has good prospects in the fields of wastewater treatment, oil-water separation, etc.

[0006] To achieve the above objectives, the present technical solution provides a method for preparing a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane, comprising the following steps:

[0007] S1. Mixing: Mixing metal organic framework ZIF-67-Co powder and polytetrafluoroethylene dispersed resin to obtain a mixture, and adding a lubricant to the mixture to prepare a paste-like material;

[0008] S2. Pressing: After the paste material is matured, the paste material is pre-pressed into a blank in a press;

[0009] S3. Extrusion and calendering: The blank is extruded through an extruder to obtain a rod-shaped object, and the rod-shaped object is calendered on a calender to obtain a base tape;

[0010] S4. Stretching and heat setting: After the base tape is degreased, it is stretched and heat-set at a certain speed to obtain a primary polytetrafluoroethylene flat film;

[0011] S5. Mineralization: The primary polytetrafluoroethylene flat membrane is mineralized with FeCl3 solution to obtain a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane.

[0012] The method for preparing a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane provided in this scheme uses metal organic framework ZIF-67-Co powder as a metal organic framework and is mixed with a polytetrafluoroethylene dispersion resin to prepare a primary polytetrafluoroethylene flat membrane. Different from traditional semiconductor photocatalytic materials (such as TiO2), the metal organic framework ZIF-67-Co can absorb visible light (absorption wavelength range is 450-650 nm, maximum absorption wavelength is 585 nm), thereby exciting internal electrons to transition from the valence band to the conduction band to form electron-hole pairs, and the electron-hole pairs further undergo redox reactions, thereby moving the absorption spectrum from the ultraviolet light absorption region (200-400nm) of traditional semiconductor photocatalytic materials to the visible light region (450-650nm), thereby achieving visible light catalysis. At the same time, the high porosity of the metal organic framework ZIF-67-Co powder can enable rapid transfer of photocharges, thereby improving the utilization efficiency of the catalyst. In addition, since the metal organic framework ZIF-67-Co powder on the surface of the primary polytetrafluoroethylene flat membrane of this scheme has strong adsorption properties and high porosity, when the primary polytetrafluoroethylene flat membrane is mineralized with FeCl3 solution, the FeOOH obtained by mineralizing the metal organic framework ZIF-67-Co powder on the surface of the primary polytetrafluoroethylene flat membrane can react with the Fenton reagent H2O2 to produce a large amount of active oxygen species, so as to improve the hydrophilicity of the composite membrane, improve the mechanical properties and anti-fouling ability, further enhance the visible light catalytic efficiency, and promote the catalytic degradation of organic pollutants. In addition, mineralized particles with other properties broaden the application range of mineralized membranes. For example, FeOOH with photocatalytic properties gives the membrane the ability to photocatalytically degrade organic pollutants.

[0013] In some embodiments, the powder particle size of the metal organic framework ZIF-67-Co powder in step S1 is 300-800 nm. Preferably, the powder particle size of the metal organic framework ZIF-67-Co powder is 300 nm, 400 nm, 500 nm, 600 nm, 700 nm and 800 nm. It should be noted that the metal organic framework ZIF-67-Co with such a powder particle size can make the ZIF-67-Co powder more easily dispersed evenly in the polytetrafluoroethylene (PTFE) matrix, avoid agglomeration, and ensure the consistency of material performance.

[0014] In some embodiments, the number average molecular weight of the polytetrafluoroethylene dispersion resin is 1 million to 10 million. Preferably, the number average molecular weight of the polytetrafluoroethylene dispersion resin is 1 million, 2 million, 3 million, 4 million, 5 million, 6 million, 7 million, 8 million, 9 million and 10 million. A higher molecular weight generally means that the PTFE material has better mechanical strength and toughness. The larger the molecular weight, the longer the polymer chain, and the stronger the interaction force between molecules, so that the material is not easy to break when subjected to external force, and the tensile strength and impact resistance of the material are improved. PTFE with a higher molecular weight exhibits a higher viscosity in the molten state, which helps to maintain the shape of the material during processing and prevent deformation or uneven film thickness caused by too fast flow, but it is also necessary to avoid that too high or too low molecular weight will affect the quality of the extruded rod. In addition, by controlling the number average molecular weight of the polytetrafluoroethylene dispersion resin, it can also help to form a uniform pore structure.

[0015] In some embodiments, the mixing conditions for mixing the metal organic framework ZIF-67-Co powder and the polytetrafluoroethylene dispersion resin to obtain the mixture are: the mixing time is 30 min~120min, and the rotating speed is 500~800r / min. Preferably, the mixing time is 30min, 40min, 50min, 60min, 70min, 80min, 90min, 100min, 110min and 120min, and the rotating speed is 500r / min, 600 r / min, 700 r / min and 800 r / min, and the mixing time and the rotating speed can be combined arbitrarily. Such an advantage is that the uniform dispersion of ZIF-67-Co powder in the PTFE dispersion resin can be ensured, while avoiding the structural damage that may be caused by excessive shearing. Such mixing conditions help to improve the quality and performance of the final product, reduce problems in the processing process, thereby improving the efficiency and reliability of the entire manufacturing process.

[0016] In some embodiments, the metal organic framework ZIF-67-Co powder is mixed with polytetrafluoroethylene dispersion resin by ball milling.

[0017] In some embodiments, the weight ratio of the metal organic framework ZIF-67-Co powder to the polytetrafluoroethylene dispersion resin is 1:100 to 1:50. Preferably, the weight ratio of the metal organic framework ZIF-67-Co powder to the polytetrafluoroethylene dispersion resin is 1:100, 1:90, 1:80, 1:70, 1:60 and 1:50. This solution controls the mass ratio of the polytetrafluoroethylene resin to be greater than the mass ratio of the metal organic framework ZIF-67-Co powder, in order to achieve effective cost control while ensuring the mechanical strength, processing performance and photocatalytic performance of the material, and to ensure the long-term stability and use effect of the material. Such a ratio setting helps to prepare a composite material with excellent performance and economic feasibility.

[0018] In some embodiments, the lubricant in step S1 is any one of aviation kerosene, paraffin oil, cyclohexane oil or naphtha, or a combination of two or more thereof.

[0019] In some embodiments, step S2 is to perform a aging treatment on the paste material by placing the paste material under certain conditions for a period of time to allow the components in the paste material to be fully mixed, so that the paste material becomes more uniform, and at the same time, the lubricant can better penetrate into the paste material to improve the fluidity and plasticity of the paste material; step S3 is to put the aging treated paste material into a blank pressing machine, and preliminarily shape the material into a blank with a certain shape and size by applying a certain pressure. Pre-pressing can improve the density of the material and reduce the risk of deformation in subsequent processing.

[0020] In some embodiments, step S3 feeds the blank into the feed port of the extruder. Under the action of heating and the screw, the blank is pushed and passes through the extrusion die to form a rod-shaped object. This process can initially give the material a certain shape and prepare for subsequent calendering. Subsequently, the extruded rod-shaped object is fed into the entrance of the calender. The thickness of the base band is controlled by adjusting the roller gap. The rod-shaped object is squeezed when passing through the roller gap and gradually flattens to form a base band. In order to ensure the flatness of the base band, it may be necessary to repeatedly calender through the calender multiple times. This process can further improve the uniformity and surface quality of the material.

[0021] In some embodiments, the degreasing temperature in the stretching and heat setting in step S4 is 160-200°C, the stretching temperature is 180-220°C, and the heat setting temperature is 380-420°C. The degreasing temperature is set at 160-200°C. This temperature range can effectively remove grease and other impurities in the base tape, ensuring that the surface of the base tape material is clean to reduce defects. Too low a temperature is not enough to completely remove grease, and too high a temperature may cause thermal degradation of the material. The heat setting temperature is set at 380-420°C. This temperature range can ensure that the material can fully crystallize during the heat setting process and improve dimensional stability. High-temperature heat setting can eliminate the internal stress generated during the stretching process and prevent the film from shrinking and deforming during use. The stretching temperature is set at 180-220°C. This temperature range can ensure that the material has good plasticity during the stretching process and is easy to stretch without breaking. Too high a temperature will cause the material to crystallize prematurely, affecting the stretching effect; too low a temperature will cause the material to be too hard and difficult to stretch.

[0022] In addition, in some embodiments, after the base tape is degreased, it is sequentially stretched longitudinally and transversely at a certain speed, and then heat-set to obtain a primary polytetrafluoroethylene flat membrane, at which time the longitudinal stretching multiple is 2 to 6 times, and the transverse stretching multiple is 5 to 8 times. The longitudinal stretching multiple is set to 2 to 6 times, which helps to improve the longitudinal mechanical strength of the membrane and improve its mechanical properties. The appropriate stretching multiple can increase the porosity of the material, improve the air permeability or flux, and maintain the strength of the membrane; the transverse stretching multiple is set to 5 to 8 times, which can significantly increase the transverse size of the membrane, thereby improving the transverse strength and toughness of the membrane, making it more stable during use and less prone to tearing.

[0023] In some embodiments, the concentration of the FeCl3 solution in step S5 is 20% to 40%. Preferably, the concentration of the FeCl3 solution is 20%, 25%, 30%, 35% and 40%. The concentration of the FeCl3 solution directly affects the efficiency of the mineralization reaction. In the concentration range of 20% to 40%, the FeCl3 solution can react well with the ZIF-67-Co powder, and the generated FeOOH can be uniformly deposited on the membrane surface. When the concentration is too low, the amount of FeOOH generated is insufficient and the performance of the membrane cannot be effectively improved; if the concentration is too high, it may cause excessive deposition of FeOOH, affecting the porosity and permeability of the membrane.

[0024] In some embodiments, in step S5, the primary polytetrafluoroethylene flat membrane is mineralized with a FeCl3 solution, and the conditions for controlling the mineralization treatment are: the mineralization time is 4 to 10 h, and the mineralization temperature is 40 to 60 ° C. Preferably, the mineralization time is 4h, 5h, 6h, 7h, 8h, 9h and 10h, and the mineralization temperature is 40 ° C, 45 ° C, 50 ° C, 55 ° C, 60 ° C, and the mineralization time and mineralization temperature can be combined arbitrarily. The main purpose of controlling the mineralization time and mineralization temperature in this scheme is to ensure that a sufficient mineralization reaction occurs between the FeCl3 solution and the ZIF-67-Co powder to generate an appropriate amount of FeOOH, thereby improving the performance of the visible light catalytic self-cleaning polytetrafluoroethylene flat membrane.

[0025] In some embodiments, the weight ratio of the medium mineralized FeCl3 solution to the primary polytetrafluoroethylene flat membrane in step S5 is 100: 1 to 50: 1. Preferably, the weight ratio of the FeCl3 solution to the primary polytetrafluoroethylene flat membrane is 100: 1, 90: 1, 80: 1, 70: 1, 60: 1 and 50: 1.

[0026] In a second aspect, the present solution provides a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane, which is prepared by the above-mentioned preparation method.

[0027] The visible light catalytic self-cleaning polytetrafluoroethylene flat membrane comprises a polytetrafluoroethylene substrate, wherein a metal organic framework ZIF-67-Co powder is formed on the surface of the polytetrafluoroethylene, and FeOOH is mineralized on the surface of the metal organic framework ZIF-67-Co powder.

[0028] Compared with the prior art, this technical solution has the following characteristics and beneficial effects:

[0029] (1) The present application obtains a polytetrafluoroethylene microporous flat membrane with visible light catalytic self-cleaning performance by loading the metal organic framework material ZIF-67-Co and surface mineralized FeOOH. The flat membrane has visible light response performance, which separates electrons and holes; at the same time, the flat membrane can synergize with the Fenton reagent H2O2 to produce a large amount of active oxygen species in the system under visible light. The metal organic framework material ZIF-67-Co has a high specific surface area, porous structure and rich functional sites, which can effectively capture and degrade Fenton reagents and organic pollutants, and has strong self-cleaning ability.

[0030] (2) This application uses a highly inert polytetrafluoroethylene microporous membrane as a visible light catalyst substrate, which can ensure the high efficiency, stability and durability of the visible light catalyst. After the polytetrafluoroethylene microporous membrane is loaded with the metal organic framework ZIF-67-Co and surface mineralized FeOOH, it has a strong self-cleaning ability, and the organic matter attached to the membrane surface is removed under visible light, so the flat membrane can be effectively recycled. After 10 cycles of cyclic oil-water separation tests under visible light, the visible light catalytic self-cleaning polytetrafluoroethylene flat membrane prepared in this application can still maintain a high oil-water separation efficiency and water flux recovery rate, showing excellent reusability and reliability, and expanding the application field of polytetrafluoroethylene flat membranes. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a scanning electron microscope image of the visible light catalytic self-cleaning polytetrafluoroethylene flat membrane obtained in Example 1.

[0032] Figure 2 This is an image of the degradation effect of the visible light catalytic self-cleaning polytetrafluoroethylene flat membrane obtained in Example 1 on the methylene blue solution.

[0033] Figure 3 This is an effect image of the oil-water emulsion separation efficiency and water flux of 10 cycles of oil-water separation using the visible light catalytic self-cleaning polytetrafluoroethylene flat membrane obtained in Example 1. DETAILED DESCRIPTION

[0034] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0035] It is to be understood that the term "one" should be understood as "at least one" or "one or more", that is, in one embodiment, the number of an element may be one, while in another embodiment, the number of the element may be multiple, and the term "one" should not be understood as a limitation on the quantity.

[0036] In the following examples, unless otherwise specified, the reagents, materials and equipment used can be purchased from commercial sources, or prepared by conventional methods, or are commonly used in the industry.

[0037] Embodiment 1:

[0038] A method for preparing a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane is prepared according to the following method:

[0039] S1. Mixing: After the metal organic framework powder ZIF-67-Co with a particle size of 300 nm and the polytetrafluoroethylene dispersion resin with a number average molecular weight of 1 million are treated with molecular sieves, they are mixed in a ratio of 1:100 using a ball mill for 30 min at a speed of 800 r / min; then the mixed powder is stirred and mixed with aviation kerosene to prepare a polytetrafluoroethylene paste material;

[0040] S2. Pressing: The paste material is matured and then pre-pressed into a polytetrafluoroethylene blank in a press;

[0041] S3 extrusion and calendering: The polytetrafluoroethylene blank is extruded through an extruder to obtain a rod-shaped object, which is then calendered on a calender to obtain a polytetrafluoroethylene tape;

[0042] S4. Stretching and heat setting: After degreasing the polytetrafluoroethylene tape at 160 °C, the tape was longitudinally stretched at a ratio of 2 and a temperature of 180 °C, and then transversely stretched at a ratio of 5 and a temperature of 180 °C, and then heat-set in a high-temperature sintering furnace at a temperature of 380 °C to obtain a primary polytetrafluoroethylene flat film with visible light catalytic performance;

[0043] S5. Mineralization: The primary polytetrafluoroethylene flat membrane is first soaked with anhydrous ethanol, and then mineralized with FeCl3 aqueous solution. The weight ratio of FeCl3 aqueous solution to primary polytetrafluoroethylene flat membrane is 100:1, the concentration of FeCl3 aqueous solution is 20%, the mineralization time is 10 h, and the mineralization temperature is 40 °C, to obtain a polytetrafluoroethylene flat membrane with visible light catalytic self-cleaning.

[0044] Embodiment 2:

[0045] A method for preparing a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane is prepared according to the following method:

[0046] S1. Mixing: After the metal organic framework powder ZIF-67-Co with a particle size of 800 nm and the polytetrafluoroethylene dispersion resin with a number average molecular weight of 10 million are treated with molecular sieves, they are mixed in a ratio of 1:50 using a ball mill, the mixing time is 120 min, and the speed is 500 r / min; then the mixed powder is stirred and mixed with paraffin oil to prepare a polytetrafluoroethylene paste material;

[0047] S2. Pressing: The paste material is matured and then pre-pressed into a polytetrafluoroethylene blank in a press;

[0048] S3 extrusion and calendering: The polytetrafluoroethylene blank is extruded through an extruder to obtain a rod-shaped object, which is then calendered on a calender to obtain a polytetrafluoroethylene tape;

[0049] S4. Stretching and heat setting: After degreasing the polytetrafluoroethylene tape at 200 °C, the tape was longitudinally stretched to 6 times at a temperature of 220 °C, and then transversely stretched to 8 times at a temperature of 220 °C, and then heat-set in a high-temperature sintering furnace at a temperature of 420 °C to obtain a primary polytetrafluoroethylene flat film with visible light catalytic performance;

[0050] S5. Mineralization: The primary polytetrafluoroethylene flat membrane was first soaked with anhydrous ethanol, and then mineralized with FeCl3 aqueous solution. The weight ratio of FeCl3 aqueous solution to primary polytetrafluoroethylene flat membrane was 50:1, the concentration of FeCl3 aqueous solution was 40%, the mineralization time was 4 h, and the mineralization temperature was 60 °C, to obtain a polytetrafluoroethylene flat membrane with visible light catalytic self-cleaning.

[0051] Embodiment 3:

[0052] A method for preparing a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane is prepared according to the following method:

[0053] S1. Mixing: After the metal organic framework powder ZIF-67-Co with a particle size of 400 nm and the polytetrafluoroethylene dispersion resin with a number average molecular weight of 3 million are treated with molecular sieves, they are mixed in a ratio of 1:80 using a ball mill, the mixing time is 60 minutes, and the speed is 700 r / min; then the mixed powder is stirred and mixed with cyclohexane oil to prepare a polytetrafluoroethylene paste material;

[0054] S2. Pressing: The paste material is aged and then pre-pressed into a polytetrafluoroethylene blank in a press;

[0055] S3 extrusion and calendering: The polytetrafluoroethylene blank is extruded through an extruder to obtain a rod-shaped object, which is then calendered on a calender to obtain a polytetrafluoroethylene tape;

[0056] S4. Stretching and heat setting: After degreasing the polytetrafluoroethylene tape at 170°C, the tape was longitudinally stretched to a ratio of 3 times at a temperature of 195°C, and then transversely stretched to a ratio of 6 times at a temperature of 195°C, and then heat-set in a high-temperature sintering furnace at a temperature of 390°C to obtain a primary polytetrafluoroethylene flat film with visible light catalytic performance;

[0057] S5. Mineralization: The primary polytetrafluoroethylene flat membrane is first soaked with anhydrous ethanol, and then mineralized with FeCl3 aqueous solution. The weight ratio of FeCl3 aqueous solution to primary polytetrafluoroethylene flat membrane is 80:1, the concentration of FeCl3 aqueous solution is 30%, the mineralization time is 8 h, and the mineralization temperature is 50 °C, to obtain a polytetrafluoroethylene flat membrane with visible light catalytic self-cleaning.

[0058] Embodiment 4:

[0059] A method for preparing a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane is prepared according to the following method:

[0060] S1. Mixing: After the metal organic framework powder ZIF-67-Co with a particle size of 700 nm and the polytetrafluoroethylene dispersion resin with a number average molecular weight of 5 million are treated with molecular sieves, they are mixed in a ratio of 1:90 using a ball mill, the mixing time is 80 min, and the speed is 650 r / min; then the mixed powder is stirred and mixed with naphtha to prepare a polytetrafluoroethylene paste material;

[0061] S2. Pressing: The paste material is aged and then pre-pressed into a polytetrafluoroethylene blank in a press;

[0062] S3 extrusion and calendering: The polytetrafluoroethylene blank is extruded through an extruder to obtain a rod-shaped object, which is then calendered on a calender to obtain a polytetrafluoroethylene tape;

[0063] S4. Stretching and heat setting: After degreasing the polytetrafluoroethylene tape at 185 °C, the longitudinal stretching ratio is 5 times, the longitudinal stretching temperature is 200 °C, and then the transverse stretching ratio is 7 times, the transverse stretching temperature is 200 °C, and then the heat setting is carried out in a high-temperature sintering furnace at a heat setting temperature of 405 °C, and finally a primary polytetrafluoroethylene flat film with visible light catalytic performance is obtained;

[0064] S5. Mineralization: The primary polytetrafluoroethylene flat membrane is first soaked with anhydrous ethanol, and then mineralized with FeCl3 aqueous solution. The weight ratio of FeCl3 aqueous solution to primary polytetrafluoroethylene flat membrane is 60:1, the concentration of FeCl3 aqueous solution is 35%, the mineralization time is 7 h, and the mineralization temperature is 55 °C, to obtain a polytetrafluoroethylene flat membrane with visible light catalytic self-cleaning.

[0065] Embodiment 5:

[0066] A method for preparing a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane is prepared according to the following method:

[0067] S1. Mixing: After the metal organic framework powder ZIF-67-Co with a particle size of 500 nm and the polytetrafluoroethylene dispersion resin with a number average molecular weight of 6 million are treated with molecular sieves, they are mixed in a ratio of 1:75 using a ball mill, the mixing time is 110 minutes, and the rotation speed is 680 r / min; then the mixed powder is stirred and mixed with aviation kerosene to prepare a polytetrafluoroethylene paste material;

[0068] S2. Pressing: The paste material is matured and then pre-pressed into a polytetrafluoroethylene blank in a press;

[0069] S3 extrusion and calendering: The polytetrafluoroethylene blank is extruded through an extruder to obtain a rod-shaped object, which is then calendered on a calender to obtain a polytetrafluoroethylene tape;

[0070] S4. Stretching and heat setting: After degreasing the polytetrafluoroethylene tape at 190 °C, the tape was longitudinally stretched to a ratio of 5 times at a temperature of 210 °C, and then transversely stretched to a ratio of 6 times at a temperature of 210 °C, and then heat-set in a high-temperature sintering furnace at a temperature of 400 °C, to obtain a primary polytetrafluoroethylene flat film with visible light catalytic performance;

[0071] S5. Mineralization: The primary polytetrafluoroethylene flat membrane is first soaked with anhydrous ethanol, and then mineralized with FeCl3 aqueous solution. The weight ratio of FeCl3 aqueous solution to primary polytetrafluoroethylene flat membrane is 75:1, the concentration of FeCl3 aqueous solution is 35%, the mineralization time is 6 h, and the mineralization temperature is 55 °C, to obtain a polytetrafluoroethylene flat membrane with visible light catalytic self-cleaning.

[0072] Comparative Example

[0073] Comparative Example 1, a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane, is different from Example 1 in that an equal amount of water is used instead of FeCl3 in the mineralization step.

[0074] Comparative Example 2, a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane, is different from Example 1 in that stirring mixing is used instead of ball milling mixing in the mixing step.

[0075] Comparative Example 3, a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane, is different from Example 1 in that the concentration of the FeCl3 solution used in the mineralization step is 5%.

[0076] Comparative Example 4, a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane, is different from Example 1 in that the concentration of the FeCl3 solution used in the mineralization step is 50%.

[0077] Comparative Example 5, a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane, is different from Example 1 in that the mineralization temperature in the mineralization step is 25°C.

[0078] Comparative Example 6, a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane, is different from Example 1 in that the mineralization temperature in the mineralization step is 70°C.

[0079] Comparative Example 7, a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane, is different from Example 1 in that an equal amount of polytetrafluoroethylene dispersion resin is used in the mixing step instead of the metal organic framework ZIF-67-Co powder.

[0080] Comparative Example 8, a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane, is different from Comparative Example 7 in that an equal amount of water is used in the mineralization step instead of the FeCl3 aqueous solution.

[0081] Performance testing

[0082] 1. Water flux test

[0083] The water flux of different polytetrafluoroethylene flat membranes was tested using a self-made cross-flow device. The test pressure was 0.1 MPa and the test time was 5 minutes.

[0084]

[0085] J is the permeation flux of the membrane (L m -2 h -1 ), V is the volume of the filtrate (L), S is the effective separation area (m 2 ), T is the fixed time (h).

[0086] 2. Dye removal efficiency test

[0087] A 20 mg / L methylene blue solution was prepared, and a homemade cross-flow device was used to test the dye removal effect of different polytetrafluoroethylene flat membranes. The dye removal rate was tested using a UV spectrophotometer. The test method is as follows: The visible light catalytic self-cleaning polytetrafluoroethylene membrane (10 g) and the dye solution (20 mg / L methylene blue solution) were placed in the dark for 30 min to reach adsorption equilibrium, 2 ml of 0.2 mmol / L hydrogen peroxide was added, and the dye solution was placed under a visible xenon lamp to trigger the catalytic process. The solution was extracted at different time points, the illumination time was 30 min, and the dye concentration was determined using a UV spectrophotometer. The corresponding formula is as follows:

[0088]

[0089] Where A represents the dye removal rate of the membrane; C represents the initial concentration of the dye; Cm The dye concentrations at different time points are indicated.

[0090] 3. Self-cleaning and anti-fouling performance test

[0091] The self-cleaning and anti-fouling performance tests used oil-water emulsions to simulate pollutants, and the oil-water separation efficiency and water flux of different polytetrafluoroethylene flat membranes in the oil-water emulsion cycle test were used to evaluate the self-cleaning performance of the membrane. After each cycle test, hydrogen peroxide was added under visible light for 30 minutes before the next cycle test was carried out, for a total of 10 cycles.

[0092]

[0093] The oil content of the emulsion and the filtrate was determined by UV-visible spectrophotometer, R was the oil-water separation efficiency, C0 and C f They are the oil contents of the oil-water emulsion before and after cross-flow separation.

[0094] The basic performance test results of various embodiments and comparative examples are shown in Table 1 below:

[0095] Table 1. Basic performance test results

[0096]

[0097] 4. Mechanical properties test of visible light catalytic self-cleaning polytetrafluoroethylene flat membrane

[0098] The tensile properties of the polytetrafluoroethylene film in this application were tested according to the method in GB / T 1040.3-2006 "Determination of tensile properties of plastics". The test sample width was 20 mm, length was 100 mm, clamping distance was 50 mm, tensile speed was 100 mm / min, each group of samples was tested five times, and the average value was taken.

[0099] The mechanical properties test results of various embodiments and comparative examples are shown in Table 2:

[0100] Table 2. Mechanical properties test results

[0101]

[0102] Analysis of test results:

[0103] By comparing Example 1 with Comparative Example 1, it can be seen that the visible light catalytic self-cleaning polytetrafluoroethylene flat microporous membrane prepared in the present application has excellent catalytic degradation of organic matter and self-cleaning and anti-fouling effects in the Fenton system. Specifically, by analyzing Example 1 with Comparative Example 1, it can be seen that the performance of the polytetrafluoroethylene flat microporous membrane that has not been mineralized in terms of dye degradation and oil-water separation is significantly reduced. The reason may be that the Fenton reaction between H2O2 and FeCOOH cannot be effectively activated, resulting in a decrease in the content of active oxygen species, thereby reducing the self-cleaning performance.

[0104] By comparing Example 1 with Comparative Example 2, it can be seen that using a ball mill to mix the metal organic framework powder and the polytetrafluoroethylene dispersion resin can effectively mix the two evenly, reduce the occurrence of metal organic framework powder agglomeration, thereby reducing the reaction active sites and greatly reducing the efficiency of pollutant degradation, and also greatly reducing the average fracture strength of the membrane.

[0105] By comparing Example 1 with Comparative Examples 3 and 4, it can be seen that the concentration of the FeCl3 solution has a significant effect on the catalytic degradation of organic matter and the self-cleaning and anti-fouling effect of the visible light catalytic self-cleaning polytetrafluoroethylene flat microporous membrane in the Fenton system, and the strength of the membrane is lost. Specifically, by analyzing Example 1 and Comparative Examples 3 and 4, when the concentration of the FeCl3 solution is low or high, the catalytic performance decreases, which may be because the mineralization of FeCOOH is incomplete or oversaturated, and the crystal defects increase, resulting in a reduction in surface active sites.

[0106] By comparing Example 1 with Comparative Examples 5 and 6, it can be seen that when mineralized at room temperature or high temperature, the catalytic performance of the membrane decreases. This may be because the purity of FeCOOH generated during the mineralization process is not high, and serious agglomeration occurs, resulting in a decrease in specific surface area, thereby reducing the active sites on the membrane surface.

[0107] By comparing Example 1 with Comparative Example 7, it can be seen that in the absence of a metal organic framework participating in the reaction, the visible light catalytic performance of the polytetrafluoroethylene microporous flat membrane is extremely low. The reason is that polytetrafluoroethylene is an inert material, and the lack of a metal organic framework causes FeCOOH to be unable to be loaded in large quantities on the surface of the polytetrafluoroethylene membrane, reducing the reaction sites between it and hydrogen peroxide, thereby greatly reducing the catalytic degradation and self-cleaning and antifouling properties of the membrane.

[0108] By comparing Example 1 with Comparative Example 8, it can be seen that in the absence of a metal organic framework and subsequent mineralization treatment steps, the polytetrafluoroethylene flat microporous membrane has no catalytic degradation effect on dyes and oil-water emulsions, so the polytetrafluoroethylene flat microporous membrane has no visible light catalytic self-cleaning effect.

[0109] The present invention is not limited to the above-mentioned optimal implementation mode. Anyone can derive other various forms of products under the inspiration of the present invention. However, no matter what changes are made in the shape or structure, all technical solutions that are the same or similar to those of the present application fall within the protection scope of the present invention.

Claims

1. A method for preparing a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane, characterized in that: The following steps are involved: S1. Mixing: Mixing metal organic framework ZIF-67-Co powder and polytetrafluoroethylene dispersed resin to obtain a mixture, adding a lubricant to the mixture to prepare a paste-like material; S2. Blank pressing: After the paste material is matured, the paste material is pre-pressed into a blank in a blank pressing machine; S3 extrusion and calendering: the blank is extruded through an extruder to obtain a rod-shaped object, and the rod-shaped object is calendered on a calender to obtain a base band; S4. Stretching and heat setting: After the base tape is degreased, it is stretched and heat-set at a certain speed to obtain a primary polytetrafluoroethylene flat film; S5. Mineralization: The primary polytetrafluoroethylene flat membrane is mineralized with FeCl3 solution to obtain a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane.

2. The method for preparing the visible light catalytic self-cleaning polytetrafluoroethylene flat membrane according to claim 1, characterized in that: The particle size of the metal organic framework ZIF-67-Co powder in step S1 is 300-800 nm, and the number average molecular weight of the polytetrafluoroethylene dispersion resin is 1 million-10 million.

3. The method for preparing the visible light catalytic self-cleaning polytetrafluoroethylene flat membrane according to claim 1, characterized in that: The mixing conditions of the mixture obtained by mixing the metal organic framework ZIF-67-Co powder and the polytetrafluoroethylene dispersed resin are as follows: the mixing time is 30 min~120 min, and the rotation speed is 500~800 r / min.

4. The method for preparing the visible light catalytic self-cleaning polytetrafluoroethylene flat membrane according to claim 1, characterized in that: The metal organic framework ZIF-67-Co powder was mixed with polytetrafluoroethylene dispersion resin by ball milling.

5. The method for preparing the visible light catalytic self-cleaning polytetrafluoroethylene flat membrane according to claim 1, characterized in that: The weight ratio of metal organic framework ZIF-67-Co powder to polytetrafluoroethylene dispersion resin is 1:100~1:

50.

6. The method for preparing the visible light catalytic self-cleaning polytetrafluoroethylene flat membrane according to claim 1, characterized in that: The lubricant in step S1 is any one of aviation kerosene, paraffin oil, cyclohexane oil or naphtha, or a combination of two or more thereof.

7. The method for preparing a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane according to claim 1, characterized in that: In step S4, the degreasing temperature during stretching and heat setting is 160-200°C, the stretching temperature is 180-220°C, the heat setting temperature is 380-420°C, and the degreasing temperature is set at 160-200°C.

8. The method for preparing the visible light catalytic self-cleaning polytetrafluoroethylene flat membrane according to claim 1, characterized in that: After the base tape is degreased, it is sequentially stretched longitudinally and transversely at a certain speed, and then heat-set to obtain a primary polytetrafluoroethylene flat film, with the longitudinal stretching multiple being 2 to 6 times and the transverse stretching multiple being 5 to 8 times.

9. The method for preparing a visible light catalytic self-cleaning polytetrafluoroethylene flat membrane according to claim 1, characterized in that: The concentration of the FeCl3 solution in step S5 is 20% to 40%.

10. A visible light catalytic self-cleaning polytetrafluoroethylene flat membrane, characterized in that: The film is prepared according to the method for preparing a visible light catalytic self-cleaning polytetrafluoroethylene flat film according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Photocatalytic boron carbide / polyvinylidene fluoride nanofilm and its preparation method

    CN113680220B

  • An AgCl / MIL-100(Fe) / PTFE photocatalytic membrane, its preparation method, and its application.

    CN114177943B

  • Composite separation membrane with photocatalytic self-cleaning function as well as preparation method and application of composite separation membrane

    CN115282787A

  • Preparation method of polytetrafluoroethylene hollow fiber composite film

    CN107469648A

  • One-step method for preparing hierarchical pore nanofiber membrane for air purification

    CN109695096A